Trajectory of the COVID-19 pandemic: chasing a moving target - Sahu, Kamal Kant (Ann Transl Med, 2020)
The spread of COVID-19 has already taken a pandemic form, affecting over 180 countries in a matter of three months. The full continuum of disease ranges from mild, self-limiting illness to severe progressive COVID-19 pneumonia, multiorgan failure, cytokine storm and death. Younger and healthy population is now getting affected than before. Possibilities of airborne and fecal oral routes of transmission has increased the concern. In the absence of any specific therapeutic agent for coronavirus infections, the most effective manner to contain this pandemic is probably the non-pharmacological interventions (NPIs). The damage due to the pandemic disease is multifaceted and crippling to economy, trade, and health of the citizens of the countries. The extent of damage in such scenarios is something that is beyond calculation by Gross Domestic Product rate or currency value of the country. Unfortunately, unlike many other diseases, we are still away from the target antiviral drug and vaccine for severe acute respiratory syndrome (SARS-CoV-2) infection. The prime importance of NPIs like social distancing, staying in home, work from home, self-monitoring, public awareness, self-quarantine, etc. are constantly being emphasized by CDC, WHO, health ministries of all countries and social media houses. This is time of introspection and learning from our mistakes. Countries like China and South Korea who were initially the most hit countries could contain the disease spread by liberal testing of their population, stringent quarantine of people under investigation and isolation of the positive cases. Rest of the countries need to act urgently as well to bring an immediate halt in the community transmission.